ANALISIS GOVERNMENTALITAS DAN REPRODUKSI WACANA DALAM SEJARAH MUNCULNYA PROGRAM KELUARGA BERENCANA DI INDONESIA TAHUN 1970 - Al Farauqi, Mohamad Dziqie Aulia (JPP (Jurnal Politik Profetik), 2022)
Abstract This article tries to apply the concept of governmentality in Michael Foucault's perspective in analyzing the Family Planning discourse which began to be implemented in 1970, precisely under the "New Order" regime under President Suharto in Indonesia. This Governmental analysis tries to reveal the existence of efforts to regulate society and change their paradigm about child ownership which in the "Old Order" regime was fully supported by the government under President Soekarno. This paper finds that the initial initiation of the Family Planning program and the discourse of small happy and prosperous families is an attempt by the new regime to change their paradigm. This paper highlights how discourse is produced, how the process works and how the process is successful in controlling the Indonesian population Keywords: Keywords; Governmentality, Discourse on Happy and Prosperous Small Family, Family Planning Program, Postmodernism